Air conditioning and mechanical ventilation (ACMV) system cost estimation using building information modeling (BIM) / Muhammad Dzulfarhi Ahmad - Ahmad, Muhammad Dzulfarhi (2021)
Lately, the construction industry has seen a shift toward Building Information Modeling (BIM) and BIM-based quantity takeoffs (QTO). BIM is quickly turning into a wellknown established collaboration process in the construction industry. Moreover, detection of clash and clash analysis during the design phase can reduce time and construction cost. This thesis presents a framework to conduct a QTO and cost estimation within the BIM environment compared to the Traditional Method (2D) for Air-Conditioning and Mechanical Ventilation system with the software interoperability. A research via survey was conducted with clients, consultants, and contractors to respond a few questions about cost estimation and BIM. Autodesk Naviswork is used to detect any clash between ACMV vs ACMV, especially in the area where big size of ducting were used, such as the basement, ground and lower ground floor. BIM 360 are used in this thesis for the purpose of sharing information with others. The result showed that by using BIM-based QTO, less items were needed compared to the traditional method. Difference in time spent for cost estimation is 120 minutes. While for the quantity, it also shows that the total difference for the area of ducting is 1.85% while the length of refrigerant pipe has a difference up to 23.58%. Clash detective features in Naviswork also detect some of the clashes and come out with the clash report. BIM 360 acts as a server and user can review the model without downloading it. Last but not least, from this research it is evident that BIM QTO method can reduce the time spent as well as quantity due to coordination.